Corn Era Hybrid Response to Nitrogen Fertilization. (1st March 2016) - Woli, Krishna P.; Boyer, Matthew J.; Elmore, Roger W.; Sawyer, John E.; Abendroth, Lori J.; Barker, Daniel W.
Abstract : Corn ( Zea mays L.) N use is of continued interest due to agronomic performance and environmental issues. This 2‐yr study evaluated era hybrid response to fertilizer nitrogen (FN) rate in a factorial arrangement of one popular hybrid per five decades (1960–2000 eras) and five N rates (0–224 kg N ha −1 ). An additional hybrid per era was grown at 168 kg N ha −1 . Hybrid productivity and nitrogen use efficiency (NUE) increased across the eras, but not between the 1980 and 1990 eras. Grain yield (GY) increased 65% and total plant biomass 43%, however, total plant nitrogen uptake (PNU) increased only 19% and across N rates was only higher for the 2000 era. At the agronomic optimum nitrogen rate (AONR), there was a linear GY increase of 0.13 Mg ha −1 yr −1 and GY N response of 0.091 Mg ha −1 yr −1, indicating considerable genetic gain. There was no trend in AONR across eras. For plant N status measures, SPAD readings decreased and canopy index values increased across eras. All NUE measures indicated significant improvement in NUE. The apparent nitrogen recovery efficiency (NRE) at N rates near the AONR of each era, however, was not highest for the most recent eras. Harvest index (HI), grain nitrogen harvest index (GNHI), and fraction of total PNU accumulated by R1 were the same among eras. The grain nitrogen concentration (GNC), however, was 24% lower for the 2000 compared to the 1960 era. Corn hybrid development across the 50‐yr period improved productivity and NUE, but not the AONR.